1995
DOI: 10.1161/01.cir.92.6.1619
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Electrograms From a Computer Model of Heterogeneously Uncoupled Anisotropic Ventricular Myocardium

Abstract: These findings confirm our hypothesis that the spatial variation of morphology of electrograms recorded simultaneously from multiple sites increases with increasing heterogeneity of intercellular coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It is well recognized that discontinuity in wavefront propagation may lead to complex polyphasic (fractionated) extracellular potential recordings. 9,26 To investigate the possibility of fractionation in extracellular recordings from ventricular tissue, we plotted extracellular potential waveforms at 28 sites throughout the rat tissue volume. The signals from the discontinuous and continuous models are shown in Figure 4 (top and bottom panels, respectively).…”
Section: Part Imentioning
confidence: 99%
“…It is well recognized that discontinuity in wavefront propagation may lead to complex polyphasic (fractionated) extracellular potential recordings. 9,26 To investigate the possibility of fractionation in extracellular recordings from ventricular tissue, we plotted extracellular potential waveforms at 28 sites throughout the rat tissue volume. The signals from the discontinuous and continuous models are shown in Figure 4 (top and bottom panels, respectively).…”
Section: Part Imentioning
confidence: 99%
“…An alternative approach to study the effect of tissue structure on electrogram morphology is to make use of computer simulation. To date, most studies have considered obstacles or inhomogeneity at the scale of 1–3 mm inside models with otherwise continuous properties 5,6,7,8 . Several studies have suggested that the spatial scale of heterogeneity is often much smaller (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations in a onedimensional (1-D) cable by Starmer et al (34,35) showed that reduced Na ϩ channel density or slowed recovery simulating electrical remodeling increased the vulnerable window (VW) for unidirectional conduction block. In addition, computer simulations investigating abnormal cell coupling on unidirectional block in 1-D cables (14, 31, 38) and conduction in two-dimensional (2-D) tissue (6,7,19,32) have demonstrated that abnormal coupling promotes unidirectional conduction block and irregular conduction. However, susceptibility to unidirectional conduction block in a 1-D cable is not equivalent to vulnerability to reentry in 2-D or three-dimensional (3-D) tissue, because, in addition to unidirectional conduction block, induction of reentry requires an alternate conduction pathway of adequate spatial dimension.…”
mentioning
confidence: 99%